The The Relevance of OJK Regulation No. 13/POJK.03/2021 to the Implementation of Shariah Restricted Investment Account Based on Mudharabah Muqayyadah in Indonesia’s Islamic Banking Law: The Relevance of OJK Regulation No. 13/POJK.03/2021 to the Implementation of Shariah Restricted Investment Account Based on Mudharabah Muqayyadah in Indonesia’s Islamic Banking Law - cholis husnah; Moh Rihul Azhar; Mohamad Rosyiful Aqli; Laili Salimah (iltizamat, 2026)
This study examines the relevance of POJK Number 13/POJK.03/2021 to the implementation of the Sharia Restricted Investment Account (SRIA) based on the mudharabah muqayyadah contract within the Indonesian Islamic banking legal system. The main academic problem addressed in this article concerns the absence of specific regulation governing SRIA as a restricted investment product, while its implementation requires legal certainty, risk governance, investor protection, and strong Sharia compliance. This research aims to analyze the extent to which POJK Number 13/POJK.03/2021 may serve as a legal basis for SRIA implementation and how the mudharabah muqayyadah contract shapes the legal relationship among fund owners, Islamic banks, and underlying investment objects. This study employs normative legal research using statutory and conceptual approaches by examining POJK provisions, the Islamic Banking Law, DSN-MUI fatwas, SRIA implementation guidelines, and relevant Islamic economic law literature. The findings indicate that POJK Number 13/POJK.03/2021 has substantive relevance as a general regulatory framework because it governs risk management, governance, internal control, transparency, and consumer protection in banking product implementation. However, the regulation remains insufficient as a specific technical basis because it does not explicitly regulate contract structure, investment restrictions, risk allocation, or legal consequences arising from violations of investor mandates. The study concludes that SRIA implementation requires an integrated framework involving POJK, DSN-MUI fatwas, technical guidelines, and Sharia supervision. The novelty of this article lies in positioning SRIA as a legal testing ground for the relationship between hard law and soft law in regulating mudharabah muqayyadah-based Islamic banking products.